White Root Disease Infected Rubber Tree Detection Through Statistical Inference of Dry Rubber Sheet Near Infrared (NIR) Spectrum Measurement Method / Noor Aishah Khairuzzaman...[et al.] - Khairuzzaman, Noor Aishah; Hashim, Hadzli; Mohd Sampian, Ahmad Faiz; Yussuf, Ummu Raihan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
In this paper, the aim of this project is to analyze the acquired information based on Near Infrared (NIR) measurement on dry rubber sheets with respect to white root disease (WRD) infected rubber tree. Then, it will be evaluated statistically using SPSS. WRD is the most serious disease where it can be spread to another tree by root to root. The tree will die slowly once it is infected by WRD. Prevention of WRD is needed to avoid higher losses in a rubber plantation. Hence, this leads the investigation in detecting WRD to overcome the problem through dry rubber sheets. Up till now there is no information and research about the WRD based on NIR spectrum through the dry rubber sheet as a subject. The measurement of NIR via dry rubber sheet using spectrometer MCS600 attached with measuring head OFK 30. NIR spectrum measurement was applied to 7 different regions of Interest (ROI) at dry rubber sheets. The outcome from measurement produces the spectrum responses which are lower peak and upper peak. The output spectrum responses obtained from the experiment are recorded and analyzed using skewness method. The SPSS software is used to analyze the skewness value. From the statistical result, it can be summarized that, healthy and WRD rubber tree can be discriminated from each other through dry rubber sheet using skewness method since the results from analysis produced significant difference at the lower peak in both cases.